Working with the potential of arts-based learning: Making sense and leaving 'business as usual' behind in an art seminar. Issue 2 (April 2022) - Flamand, Guillaume; Perret, Véronique; Picq, Thierry
The purpose of this study is to contribute to the interest in arts-based learning as part of the growing literature on artistic initiatives in business contexts, by advancing the understanding of the potential of arts-based business learning that people can yet fail to benefit from. We draw on Weick's framework for how people construct meaning in organized situations and on a qualitative study of an art seminar in business education to consider arts-based learning in the face of pitfalls that can prevent people from engaging in approaches that differ from their usual ones and from which they can learn. We show that people can benefit from the potential of arts-based business learning when collective meaning-construction processes such as sensemaking or sensegiving can unfold and work in an iterative, active and intense way, to take people towards new experiences. Our study also highlights the usefulness of taking a perspective centred on ongoing collective meaning-construction processes and of focusing on both learning activities and learning situations when studying business learning.